Biotechnologies for Marine Oil Spill Cleanup: Indissoluble Ties with Microorganisms. Issue 9 (September 2017) - Mapelli, Francesca; Scoma, Alberto; Michoud, Grégoire; Aulenta, Federico; Boon, Nico; Borin, Sara; Kalogerakis, Nicolas; Daffonchio, Daniele
Abstract : The ubiquitous exploitation of petroleum hydrocarbons (HCs) has been accompanied by accidental spills and chronic pollution in marine ecosystems, including the deep ocean. Physicochemical technologies are available for oil spill cleanup, but HCs must ultimately be mineralized by microorganisms. How environmental factors drive the assembly and activity of HC-degrading microbial communities remains unknown, limiting our capacity to integrate microorganism-based cleanup strategies with current physicochemical remediation technologies. In this review, we summarize recent findings about microbial physiology, metabolism and ecology and describe how microbes can be exploited to create improved biotechnological solutions to clean up marine surface and deep waters, sediments and beaches. Trends: Cleaning up oil spills in marine environments ultimately relies on microbial metabolism of HC, which complements the current chemicophysical techniques used in emergency response. Consolidated biotechnologies include microbial communities biostimulation, biosurfactant supplementation and bioaugmentation HC-degrading microbial cells. The effectiveness of biotechnologies is limited by our understanding of the microbial ecology of polluted marine systems. We lack knowledge on how environmental factors, such as hydrostatic pressure, temperature and dispersant toxicity, affect microbial successions. The recent availability of meta-omics data and the improved understanding of microbial metabolism are leading to novel biotechnologies for marine oil spill cleanup, such as slow-release particles for efficient biostimulation and bioelectrochemical approaches for sediment cleanup.